UMP bags 19 gold medals conferred ITEX Golden Award - Mimi Rabita, Abdul Wahit (2021)
KUALA LUMPUR, 14 December 2021 - Universiti Malaysia Pahang (UMP) won the ITEX Golden Award for winning 19 gold, nine silver, and two bronze medals in the International Invention, Innovation & Technology Exhibition (ITEX) 2021 held at the Kuala Lumpur Convention Centre (KLCC).